CMET-17. RENAL CELL CARCINOMA BRAIN METASTASES TREATED WITH STEREOTACTIC RADIATION THERAPY AND NIVOLUMAB DOES NOT ALTER LESIONAL OR CLINICAL OUTCOMES. (11th November 2019) - Mohammadi, Homan; Tolpin, Aaron; Figura, Nicholas; Peacock, Jeffrey; Oliver, Daniel; Sim, Austin; Palm, Russel; Ahmed, Kamran; Liu, James; Tran, Nam; Etame, Arnold; Vogelbaum, Michael; et al.
Abstract: Metastases (BM) carries the risk of hemorrhaging lesions and can be effectively treated using stereotactic radiotherapy (SRT). Nivolumab is a recently approved immunotherapy for stage IV RCC. We evaluate whether patients with RCC BM treated with SRT overlapping with nivolumab have altered clinical and BM outcomes. METHODS: 38 consecutive patients were identified in our retrospective database from 1/2011 to 6/2018. Analyses were performed on a per-lesional basis (n=170), per-treatment session basis (n=79), and per-patient basis (n=38). Patients who received nivolumab within 6 months of SRT were considered to have overlapping treatments. ROC curve, chi-squared, Kaplan-Meier, log-rank, and Cox regression model were employed for statistical analyses. RESULTS: A total of 7 (18.4%) patients received overlapping treatments for 64 (37.6%) eligible lesions. Median follow-up was 15.4 months and median overall survival from first BM treatment was 14.8 months (0.5 – 98.4). Median time to subsequent distant brain and non-brain failures were 3.4 and 2.2 months, respectively. Median time to local failure was 20.2 months (two lesions). There were 11 hemorrhagic toxicities (7 in the nivolumab group) and 17 radionecrosis toxicities (4 in the nivolumab group) with no significant difference amongst the groups. Lesions receiving nivolumab within 6 months of SRT did not exhibit a higher rate of toxicity (p=0.521) but had a shortened time to hemorrhage (p< 0.001). Patients who received SRT > 1 month after nivolumab had a prolonged time to subsequent distant brain failure (median 11.1 months) than patients who received SRT > 1 month before (median 3.1 months) or within 1 month (median 1.6 months) of nivolumab, p=0.014. CONCLUSIONS: Overlapping nivolumab with SRT is safe with no increased risk of hemorrhagic lesions. An optimal treatment sequence of nivolumab administration followed by SRT prolongs the time to subsequent BM and warrants further investigation.